Post-Completion Audits of Investment Projects in Mining Companies - SERGEEV, Igor; LEBEDEVA, Olesia; EVSEENKO, Violetta (Journal of Advanced Research in Law and Economics; Vol 8 No 4(26) (2017): JARLE Volume 8 Issue 4(26) Summer 2017, 2017)
The paper is aimed at developing the analytical framework for post-completion auditing (PCA) of mining companies’ investment projects, which considers their particular nature, enables comparison of ex ante and ex post data, and quantitative assessment of the key external and internal factors’ impact on performance indicators of commissioned mining projects. Within the research, four types of effects were revealed and assessed by means of factor analysis techniques along with the discounted cash flows method. Changes in business environment, mineral reserves estimates, operational expenditures, as well as cost of capital were considered as underpinning of the mentioned effects emergence. The results of the investigation contribute to theoretical development of a dynamic approach to evaluation and management of long-term mining projects. Besides, the designed analytical framework for PCA can be beneficial for capital budgeting practices of mining companies as the element of the dynamic project management system.